Incidentally Diagnosed Asymptomatic COVID-19 Does Not Increase Total Complication Risk in Total Joint Arthroplasty - Vaibhav R. Tadepalli, MD; Jasraj S. Raghuwanshi, BS; Wendy Novicoff, PhD; James A. Browne, MD; Ian M. Duensing, MD (Arthroplasty Today, 2025)
Background: Impacts of asymptomatic perioperative coronavirus disease 2019 (COVID-19) on total knee (TKA) and hip arthroplasty (THA) outcomes remains unknown. Methods: We retrospectively reviewed asymptomatically screened COVID-19 cases undergoing primary TKA or THA between 2020 and 2022. Ninety-day complications, inpatient resources, repeat hospitalizations, and functional outcomes were measured for COVID-19 patients and age- and sex-matched controls. The sample size was determined based on a priori power analysis. Statistics consisted of 2 sample t-tests or Fisher’s exact test based on variable type with α = 0.01 to correct for multiple comparisons. Results: Of 1914 TKA and 1424 THA patients, 20 and 28 with asymptomatic COVID-19 were compared to 75 and 105 controls, respectively. While there was no statistically significant increase in relative risk for major (TKA P = .04|THA P = .12) or thromboembolic (TKA P = .21|THA P = .04) complications, the COVID-19 group experienced mortality, ischemic stroke, pulmonary embolism, and deep vein thrombosis. There was no significant difference in admission length (TKA P = .29|THA P = .22), physical therapy (TKA P = .36|THA P = .36), labs (TKA P = .57|THA P = .82), nonhome discharge (TKA P = 1|THA P = 1), or mobility (TKA P = .18|THA P = .21). Conclusions: The current study suggests that, while perioperative risk of asymptomatic COVID-19 does not meet the threshold for statistical significance, arthroplasty surgeons should be aware of potential mortality and morbidity and engage in shared decision-making regarding deferral of surgery, especially for patients with other comorbidities.